Sociodemographic and clinical factors associated with cryptorchidism in live births in Brazil: a 20-year analysis - Diego Bessa Dantas; Dionata da Costa; Edila Andrade; Maria do Socorro Bastos; Fabiana Gomes; João Simão de Melo-Neto (SAGE Publishing, 2021)
Background: Cryptorchidism is a congenital disorder that causes an irregularity in the permanent or temporary descent of one or both testicles. In Brazil, there are no comprehensive studies describing the association of demographic, social, and clinical characteristics in relation to cryptorchidism. Objectives: This study aims to verify possible associations of clinical and sociodemographic characteristics in patients with cryptorchidism. Design and Methods: An analytical, descriptive and retrospective study was carried out based on secondary data of 5,168 live births with cryptorchidism recorded in the Live Birth Information System (SINASC), Brazil from 1999 to 2018. The socio-demographic factors analyzed were the geographic region, age, education and marital status of the mothers. The clinical factors analyzed were the duration and type of pregnancy. The place of birth was also analyzed as a secondary outcome. Results: This research analyzed all live births during the study period, in Brazil. The chance of cryptorchidism in the neonate is more common in women who become pregnant later (≥30 years of age) and with a higher level of education (≥8 years). The risk of cryptorchidism in relation to the federation units is higher in Paraíba, Pernambuco, Sergipe, São Paulo, and Santa Catarina. Regarding the clinical characteristics, the shorter pregnancies, which characterize premature births, are a risk for the appearance of cryptorchidism in the country. Conclusion: Thus, in this study, we found that sociodemographic and clinical factors have specific characteristics that predict cryptorchidism in newborns in Brazil.